ANALISIS CUSTOMER CONTACT DAN SERVICE GUARANTEE TERHADAP CUSTOMER SATISFACTION DENGAN CUSTOMER VALUE SEBAGAI VARIABEL INTERVENING - Maladzi, Fahmi Haikal; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2015)
The background of this research is the reduction of direct interaction and a guarantee that the company gave notice to the customer. This study aims to determine how much influence customer contact and service guarantee to customer satisfaction with customer value as an intervening variable in train service users operating area 4 Semarang.            The number of samples in thie study are 100 respondents train service users ho were selected based on purposive sampling method. The questionnaire is distribute in April 2015. The data obtained are processed using validity and reliability test, classic assumption test, multiple regression analysis, goodness of fit test with regression coefficients, test F and test T.            The result of this study showed that the variables of customer contact provide value 43,6% and service guarantee provide value 42,7% which both have a positive and significant impact on customer value. Then customer contact provide value 25,8% and customer value with a  value of 62,7% which both have a positive and significant impact on customer satisfaction, while service guarantee with a value of 1,4% have a positive effect but not significant on customer satisfaction.